Effects of perceptions of corporate social performance on individual purchasing behaviour in South African university students: A mixed-method approach - Roselyne Koech; David Coldwell (South African Journal of Business Management, 2019)
Background: Corporate social performance (CSP) has been widely researched in the past. However, few empirical studies, especially in the African context, have been conducted. In particular, a highly under-researched topic is the role that corporate social responsibility (CSR) plays in an individual's actual purchasing behaviour.Objectives: This article examines whether the perception of CSR plays a role in purchasing decisions of South African university students. It adopts Carroll's CSR definition that comprises economic, legal, ethical and philanthropic responsibilities.Methods: A mixed-method technique was used to analyse the data obtained from a sample survey (n = 145) and in-depth interviews (n = 30) of South African university students. An exploratory factor analysis was performed which revealed that legal, ethical and philanthropic factors influence individual purchasing behaviour.Results: The findings show that companies that fulfil consumer expectations of social responsibility tend to generate positive perceptions of CSP, which lead to actual purchases of goods and services from the company concerned. The findings also show that CSR plays a relatively minor role in individuals' actual purchasing behaviour, and the other-than-CSP aspects influencing the outcome are explained.Conclusion: The study extends the theoretical understanding of CSR and its role in purchasing decisions of individuals in the African context.
Keywords: 650